A Talmud in exile : the Influence of Yerushalmi Avodah Zarah on the formation of Bavli Avodah zarah - Gray, Alyssa M. (Brown Judaic studies, 2020)
"This book is a targetted study engaging the widely known phenomenon that many tractates in the Babylonian Talmud exhibit broad similarities to their counterparts in the Palestinian Talmud. Gray argues that this is the result of the production of an "early Talmud" in Palestine that made its way to Babylonia, where it formed later Babylonian editors used it in building the Babylonian Talmud."--Provided by publisher